2012
DOI: 10.1007/s10072-012-1048-3
|View full text |Cite
|
Sign up to set email alerts
|

Headache, eating and sleeping behaviors and lifestyle factors in preadolescents and adolescents: preliminary results from an Italian population study

Abstract: Several dietary and lifestyle habits can be associated with headaches or with their progression to chronic forms in adults. We report the results of the first population study performed in Italy on a sample of preadolescent and adolescent students to assess the possible association between headache and specific habits and lifestyle factors. Preliminary data from 800 questionnaires showed that 365 subjects had headaches, which were of moderate-severe intensity, associated with anorexia, and caused absence from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 14 publications
1
16
1
Order By: Relevance
“…Recently, we reported the preliminary results of the first population-based study [47] performed in Italy on preadolescent/adolescent students to assess the possible association between headache and specific habits or lifestyle factors. The data obtained from 800 students, divided in two groups (with headache and without headache), showed that headache patients were prevalently women (P value = 0.006), irregular meal consumers (P \ 0.0001), particularly breakfast (P \ 0.0001) and reported more frequent sleep disorders (P \ 0.0001).…”
Section: What We Know About Adolescentsmentioning
confidence: 99%
“…Recently, we reported the preliminary results of the first population-based study [47] performed in Italy on preadolescent/adolescent students to assess the possible association between headache and specific habits or lifestyle factors. The data obtained from 800 students, divided in two groups (with headache and without headache), showed that headache patients were prevalently women (P value = 0.006), irregular meal consumers (P \ 0.0001), particularly breakfast (P \ 0.0001) and reported more frequent sleep disorders (P \ 0.0001).…”
Section: What We Know About Adolescentsmentioning
confidence: 99%
“…Milde‐Busch et al () did not find any connection between skipping meals or insufficient fluid intake and headache in adolescents. However, Moschiano et al () found a clear association between headache and irregular intake of meals (especially breakfast) and sleep disturbances, with a worsening of headaches. There is good evidence that improved sleep routines have a positive effect on children and young people with migraines (Bruni, Galli, & Guidetti, ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, Moschiano et al indicated that individuals with headache had irregular meals (especially irregular breakfast) and sleep disturbance compared to those without headache (38). Most studies mentioned above evaluated the different types of headaches, not just the primary headaches, and were performed on adolescences.…”
Section: Discussionmentioning
confidence: 99%